scFv-Anti-LDL(-)-Metal-Complex Multi-Wall Functionalized-Nanocapsules as a Promising Tool for the Prevention of Atherosclerosis Progression - Cavalcante, Marcela Frota; Adorne, Márcia Duarte; Turato, Walter Miguel; Kemmerer, Marina; Uchiyama, Mayara Klimuk; Asbahr, Ana Carolina Cavazzin; Alves, Aline de Cristo Soares; Farsky, Sandra Helena Poliselli; Drewes, Carine; Spatti, Marina Cecília; Kazuma, Soraya Megumi; Boss, Marcel; et al. (Frontiers in Medicine, 2021)
Atherosclerosis can be originated from the accumulation of modified cholesterol-rich lipoproteins in the arterial wall. The electronegative LDL, LDL(-), plays an important role in the pathogenesis of atherosclerosis once this cholesterol-rich lipoprotein can be internalized by macrophages, contributing to the formation of foam cells, and provoking an immune-inflammatory response. Herein, we engineered a nanoformulation containing highly pure surface-functionalized nanocapsules using a single-chain fragment variable (scFv) reactive to LDL(-) as a ligand and assessed whether it can affect the LDL(-) uptake by primary macrophages and the progression of atherosclerotic lesions in Ldlr-/- mice. The engineered and optimized scFv-anti-LDL(-)-MCMN-Zn nanoformulation is internalized by human and murine macrophages in vitro by different endocytosis mechanisms. Moreover, macrophages exhibited lower LDL(-) uptake and reduced mRNA and protein levels of IL1B and MCP1 induced by LDL(-) when treated with this new nanoformulation. In a mouse model of atherosclerosis employing Ldlr-/- mice, intravenous administration of scFv-anti-LDL(-)-MCMN-Zn nanoformulation inhibited atherosclerosis progression without affecting vascular permeability or inducing leukocytes-endothelium interactions. Together, these findings suggest that a scFv-anti-LDL(-)-MCMN-Zn nanoformulation holds promise to be used in future preventive and therapeutic strategies for atherosclerosis.